Can India emulate China in attracting and benefitting from FDI? - Karl P. Sauvant; Daniel Allman (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2016)
Over the last forty years, China's economic growth and rates of FDI have vastly outstripped India's. As India seeks to boost foreign investment with its "Make in India" campaign, this Perspective considers the possible lessons from China's experience and recommends matching regulatory reform with coordinated investment promotion.
Keywords: 330